Variable contribution of wood to the hydraulic resistance of headwater tropical streams. Issue 8 (5th August 2013) - Cadol, Daniel; Wohl, Ellen
<x xml:space="preserve">Abstract</x> [1] We investigated the relative contribution of wood to total flow resistance in a tropical setting by measuring wood load and hydraulic resistance in six forested headwater sites at a range of subformative discharges. We evaluated the effectiveness of wood in increasing resistance by comparing measured velocity with predicted velocity from nondimensional hydraulic geometry equations that include slope, unit discharge, and either bed grain size (D84) or bed elevation variation (σt). The predictive equation that uses D84 as the characteristic roughness length successfully predicts velocity in the steep, coarse‐bed study reaches, but greatly overpredicts velocity in the low‐energy, sand‐bed study reaches. The degree of overprediction correlates with a dimensionless wood load metric (α*), which incorporates projected area of wood per unit volume of flow in the reach (α) and average wood diameter (dave). We use this correlation to suggest a wood load adjustment factor for the D84‐based predictive equation. The equation that uses σt as the roughness length successfully predicted velocity in the sand‐bed reaches, where large wood pieces incorporated into the bed and oriented perpendicular to flow cause most bed elevation variation. In our study sites, frequent and flashy floods appear to reorganize the wood in high‐energy reaches, leaving wood that is concentrated in low‐velocity zones along the channel margins and streamlined to flow, thus reducing wood resistance compared to similar streams in snowmelt‐dominated or spring‐fed hydrologic settings. However, in our low‐energy, sand‐bed study reaches, wood contributes strongly to flow resistance by increasing channel bed and margin complexity.